O conhecimento da verdade e suas bases conceptuais metafóricas - Lima, Carmen Rita Guimarães Marques de (2010)
The present study focuses on the Idealized Cognitive Model (ICM) of Truth, expressed linguistically in written texts in Brazilian Portuguese, and it aims at investigating the metaphorical processes involved in its structure. The research is theoretically founded on Sociocognitive Linguistics, Conceptual Metaphor Theory (as in Lakoff and Johnson, 1980, 1999), as well as on studies concerning the relationship between metaphor and culture (Kövecses 2005, 2006; Deignan, 2003; Tomasello, 2003 [1999] and Gibbs, 1997). The analysis drew on two corpora. The first, which consisted of journalistic texts about the political fact known as the mensalão , enabled the identification of a set of linguistic items, named metaphors of truth . The second included non-journalistic texts from different genres, collected from media-focused websites as well as blogs which discuss general affairs which circulate in the media. Two data collection procedures were used: the texts from the original corpus were submitted to metaphor identification through vehicle (MIV, CAMERON, 2003, 2006), and, at a later stage, the metaphorical expressions were used as input for obtaining new data, through the use of Google. This allowed for the mapping of metaphorical expressions in other discursive environments and the identification of new metaphors of truth. The data analysis indicates a significant occurrence of linguistic expressions which constitute a coherent set of metaphorical uses, revealing a particular folk understanding of the concept of truth. The mapping of such uses led to an identification of a metaphorical system which structures and organizes the ICM of the knowledge of truth, which forms a complex whole, consisting of two submodels: the submodel of discovering and the submodel of covering. The conceptual organization of this ICM mobilizes processes of figurative projection, among which we identified the image schemata of imposition and removal of the object, the ontological metaphor TRUTH IS AN OBJECT, the primary metaphors KNOWING IS SEEING and VISUAL FIELDS ARE RECIPIENTS, which, in interaction with the folk theories of essence and of intelligibility, allow for another conceptual metaphor: KNOWING IS SEEING THE TRUTH.